Antimitotic activity of EA21b mammary-carcinoma extract - Flamini, Mirta Alicia (2007)
Many tumors produce factors that affect cell-cycle and cell proliferation. In the present study we have analyzed the effect of a mammary-tumor extract injection on the mitotic activity of several organs in young male C3H/S mice previously standardized for circadian periodicity. One-half of the animals received an intraperitoneal EA21b tumor extract dose at 16:00 h, while the other half received saline. Animals were sacrificed on the following day at 08:00, 12:00 or 16:00 h. 4 h after receiving an injection of colchicine by the same route. Samples of duodenum, kidney, liver, and submaxillary gland were excised and processed for hematoxylin-eosin staining. Mitotic indices, expressed as the number of colchicine-arrested metaphases per 1,000 nuclei, were assessed in convoluted tubule epithelium, duodenal crypt enterocytes, hepatocytes and submaxillary gland ductal and acinar sialocytes. All values were expressed as mean ± SEM. Statistical analyses were performed by ANOVA, Bonferroni and Student's t-tests. In contrast to the mitotic indices reductions observed in renal convoluted tubules cells and duodenal crypt enterocytes, neither the submaxillary gland nor the liver were found to contain cell types whose mitotic activity was affected by the tumor extract. We conclude that EA21b mammary carcinoma contains one or more factors that inhibit the proliferation of selected populations of normal cells.